2015
DOI: 10.1016/j.cell.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Function of Regulatory T Cells in Tissue Protection

Abstract: SUMMARY Regulatory T (Treg) cells suppress immune responses to a broad range of non-microbial and microbial antigens and indirectly limit immune inflammation-in-flicted tissue damage by employing multiple mechanisms of suppression. Here, we demonstrate that selective Treg cell deficiency in amphiregulin leads to severe acute lung damage and decreased blood oxygen concentration during influenza virus infection without any measureable alterations in Treg cell suppressor function, antiviral immune responses, or v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
837
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 806 publications
(882 citation statements)
references
References 35 publications
38
837
3
4
Order By: Relevance
“…Following intramuscular injection of cardiotoxin as a model of induced tissue damage following acute injury in mice, the authors unveiled the important role of Tregs in muscle tissue protection, repair, and maintenance. This mode of action seems to be independent of their immunosuppressive functions (Arpaia et al ., 2015). Interestingly, transient accumulation of senescent myogenic cells is also required for proper muscle repair and participates in the process of skeletal muscle regeneration as well (Le Roux et al ., 2015).…”
Section: Cellular Senescence and Immunity In Tissue Homeostasismentioning
confidence: 99%
“…Following intramuscular injection of cardiotoxin as a model of induced tissue damage following acute injury in mice, the authors unveiled the important role of Tregs in muscle tissue protection, repair, and maintenance. This mode of action seems to be independent of their immunosuppressive functions (Arpaia et al ., 2015). Interestingly, transient accumulation of senescent myogenic cells is also required for proper muscle repair and participates in the process of skeletal muscle regeneration as well (Le Roux et al ., 2015).…”
Section: Cellular Senescence and Immunity In Tissue Homeostasismentioning
confidence: 99%
“…3,9 IL-33 binding to the IL-33/ST2 receptor produces pro-inflammatory cytokines and Th2 cytokines. 12 McHedlidze et al 11 demonstrated increased IL-33 production on liver injury, activating ILC2s with IL-13 production signaling via the IL-4 receptor and transcription factor STAT6 activation, as a critical downstream pathway of IL-33-dependent pathologic tissue remodeling and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In context to EIMD, FAP-like cells become activated and release IL-33. The release of IL-33 promotes the M1 to M2 polarization of macrophages; and induces the release of the growth factor amphiregulin from tissue resident T reg cells, which can be responsible for the differentiation of satellite cells within the muscle and muscle repair [12,60]. There is limited information on the release of IL-33 in response to exercise and nothing is known about the effects of IL-33 release in response to intensity or volume of exercise.…”
Section: Recognition Of Exercise Induced Muscle Damage and Innate Immmentioning
confidence: 99%
“…Recent studies have identified the requirement for IL-33 in homeostasis of tissue derived Tregs in the muscle [52,54]. Importantly the tissue Tregs do not require TCR signals for activation, but instead, rely on the secretion of IL-33 from damaged cells and cytokine signaling for their activation and function to facilitate tissue repair through their ability to secrete amphiregulin [12,52,54]. Therefore tissue Tregs have developed a specialized function in sensing changes in their environment to limit inflammation and promote repair [55].…”
Section: Inflammation and Tissue Repairmentioning
confidence: 99%
See 1 more Smart Citation